Comparison of Embankment Reinforcement Requirements with Geotextile on Soft Soil with 2D and 3D Slope Stability Analysis Methods - Nur ‘ Arfiati Shoffiana; Yudhi Lastiasih; Trihanyndio Rendy Satrya (Journal of Infrastructure & Facility Asset Management, 2022)
Slope stability analysis is very important in slope design so it can manage and maintain the infrastructure assets. If the slope is unstable, it can damage the infrastructure around the slope. The method commonly used in slope stability analysis is 2D modeling which assumes the length of the landslide area is not limited or continuous. In fact, landslides that occur in the field are limited and not continuous, so 3D modeling is more suitable than 2D modeling. 3D slope stability analysis has been developed by various researchers. Most of the results of previous studies stated that the 3D and 2D factor of safety ratio was more than one for cohesive soils and less than one for non-cohesive soils. This safety factor affects the amount of reinforcement needed. Differences in 2D and 3D safety factors will cause differences in the amount of reinforcement needed. Therefore, this study was conducted to determine the differences in the 2D and 3D slope stability analysis result. Slope stability analysis was carried out using LEM, where the 2D slope stability used the Fellenius method while the 3D slope stability used the Hovland method. Calculate the required reinforcement amount using geotextiles with Tult = 250 kN/m. The results obtained from this study are the 2D safety factor is smaller than the 3D safety factor. The 3D and 2D safety factor ratios range from 1.09 – 1.397. While the amount of reinforcement required in the 3D analysis is less than in the 2D analysis with the ratio of 3D and 2D reinforcement requirements ranging from 0.5 to 0.955 depending on the width and height of the embankment.